Interval Type-2 Fuzzy Dynamic High Type Control of Permanent Magnet Synchronous Motor with Vector Decoupling Method - Xinglong Chen (MDPI AG, 2021)
This paper presents an interval type-2 fuzzy dynamic high type (IT2FDHT) control based on vector decoupling method for permanent magnet synchronous motor (PMSM) to improve the dynamic characteristics of the system. Firstly, to address the shortcomings of the traditional PI regulator used in the current loop of PMSM, an improved PI regulator based on voltage feed-forward decoupling is used. Then, considering the characteristics that the higher the system type, the smaller the steady-state error and the shorter the regulation time, the high type control structure is added. However, a purely high type structure amplifies the oscillations of the system and is extremely sensitive to perturbations, which can easily lead to system divergence. Therefore, in order to solve the problems caused by high type structure, finally we designed dynamic high type control with the help of fuzzy logic systems (FLSs), which successfully achieved automatic switching of system type while improving response speed and steady-state accuracy. Meanwhile, quantum-behaved particle swarm optimization (QPSO) algorithm is employed to determine the parameters of FLSs. In summary, five methods including conventional PI, feed-forward decoupling PI (FDPI), FDPI high type (FDPI-HT), FDPI type-1 fuzzy dynamic high type (FDPI-T1FDHT), and FDPI-IT2FDHT, are compared to show the superiority of the proposed method. By means of simulations, the excellence of proposed FDPI-IT2FDHT is verified.